Local fiscal policies and their impact on the number and spatial distribution of new firms - Riedel, N; Simmler, M; Wittrock, C (Elsevier, 2020)
We examine the effect of local business taxation and local public good and service (PIGS) provision on the number and spatial distribution of new firms. Testing ground is Germany and we rely on the universe of firm foundations between 1998 and 2006. Methodologically, we estimate fixed effects poisson models coupled with a control function approach. The results suggest that a 1%-decrease in the business tax rate (the PIGS capital stock) raises (lowers) the number of new firms in the policy-changing jurisdiction by 4.6% (0.8%). Business tax reductions, moreover, strongly reduce the number of firm foundations in neighboring municipalities, implying that the aggregate number of new firms remains unchanged; while PIGS provision, on average, does not impact the number of firms in adjacent jurisdictions, negative effects emerge for subsets of PIGS and firms.